The Impact of Leader-Member-Exchange and Competency on Performance with Organizational Citizenship Behavior as a Mediation Variable for Academic Staff of Private Universities In Kalimantan Region - Diana Hayati; Hari Nugroho Akimas; Rini Rahmawati (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Abstract This study wanted to determine the impact of leader-member exchange (LMX) and Competence on performance with organization citizenship behavior (OCB) as a mediating variable in private university academic staff. Data was collected through an online survey of staff working at private universities totaling 75 people and analyzed using structural equation models (PLS). The findings show a direct influence for LMX variables on OCB, Competence on OCB, LMX on performance, Competence on performance, and OCB on performance, which has a positive and significant effect. While indirect influence can be seen from the impact of competency variables on performance through OCB, it is 0.095 (positive) with a P-value of 0.061 > 0.05 (not significant), meaning that OCB variables do not play a role in mediating the influence of Competence on performance. The second variable has an indirect effect of the LMX variable on performance through OCB 0.179 (positive) with a P-value of 0.012 < 0.05 (significant), meaning that the OCB variable plays a role in mediating the effect of LMX on performance. The limitation of this paper is that it only uses 75 respondents from academic staff in private universities in the South Kalimantan and Central Kalimantan regions; for future research, more respondents can be used, and a wider area of respondents can be used. Keywords: LMX, Competence, OCB and Performance